Intraoperative Blood Transfusion Is Associated With Increased Risk of Venous Thromboembolism After Radical Cystectomy. Issue 3 (29th March 2023) - Myers, Amanda; Frank, Igor; Shah, Paras H.; Tarrell, Robert F.; Baird, Bryce; Dora, Chandler; Karnes, R. Jeffrey; Thompson, R. Houston; Tollefson, Matthew K.; Boorjian, Stephen A.; Lyon, Timothy D.
Abstract : Purpose: Our objective was to examine whether perioperative blood transfusion is associated with venous thromboembolism following radical cystectomy adjusting for both patient- and disease-related factors. Materials and Methods: Patients who underwent radical cystectomy for bladder cancer from 1980-2020 were identified in the Mayo Clinic cystectomy registry. Blood transfusion during the initial postoperative hospitalization was analyzed as a 3-tiered variable: no transfusion, postoperative transfusion alone, or intraoperative with or without postoperative transfusion. The primary outcome was venous thromboembolism within 90 days of radical cystectomy. Associations between clinicopathological variables and 90-day venous thromboembolism were assessed using multivariable logistic regression, with transfusion analyzed as both a categorical and a continuous variable. Results: A total of 3, 755 radical cystectomy patients were identified, of whom 162 (4.3%) experienced a venous thromboembolism within 90 days of radical cystectomy. Overall, 2, 112 patients (56%) received a median of 1 (IQR: 0-3) unit of blood transfusion, including 811 (38%) with intraoperative transfusion only, 572 (27%) with postoperative transfusion only, and 729 (35%) with intraoperative and postoperative transfusion. On multivariable analysis, intraoperative with or without postoperative blood transfusion was associated with a significantly increased risk of venous thromboembolism (adjusted OR 1.73, 95% CI 1.17-2.56, P = .002). Moreover, when analyzed as a continuous variable, each unit of blood transfused intraoperatively was associated with 7% higher odds of venous thromboembolism (adjusted OR 1.07, 95% CI 1.01-1.13, P = .03). Conclusions: Intraoperative blood transfusion was significantly associated with venous thromboembolism within 90 days of radical cystectomy. To ensure optimal perioperative outcomes, continued effort to limit blood transfusion in radical cystectomy patients is warranted.